1993
DOI: 10.1136/bmj.307.6910.972
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Society's APACHE II study in Britain and Ireland--I: Variations in case mix of adult admissions to general intensive care units and impact on outcome.

Abstract: Objectives-To describe the extent of variation in the case mix of adult admissions to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
5

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 18 publications
4
72
0
5
Order By: Relevance
“…Although the same data set was used, the APACHE II results were different from those of the original APACHE II study carried out by Rowan et al [2][3][4][5]. This is because only a third of the total data set (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although the same data set was used, the APACHE II results were different from those of the original APACHE II study carried out by Rowan et al [2][3][4][5]. This is because only a third of the total data set (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…The study was conducted using the database collected for the ICS UK APACHE II study [2][3][4][5]. This data set contains the physiological variables required to calculate the APACHE II score and the hospital mortality for 8796 patients from 26 ICUs in the UK and Ireland.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering individual outcome prediction, the calibration at the highest risks of death is of interest. In the UK, Beck et al [13] have shown that the APACHE II system's calibration is better overall than that of the APACHE III and MPM models; even so calibration of the APACHE II system at the highest risks of death is not perfect as the system tends to overestimate actual mortality [14]. This is clearly not satisfactory when attempting to decide whether withdrawal of treatment is appropriate.…”
Section: Accuracymentioning
confidence: 99%